Successful use of a bivalirudin treatment protocol to prevent extracorporeal thrombosis in ambulatory hemodialysis patients with heparin‐induced thrombocytopenia. Issue 2 (26th October 2015) - Al‐Ali, Fadwa Saqr; Elsayed, Mohammed; Khalifa, Sabah; Abdulla, Aisha Elsayed; Tolba, Hoda; Bouanane, Hisham; Ibrahim, Rania; Hamad, Abdullah
Abstract: Heparin‐induced thrombocytopenia (HIT) is an uncommon problem in hemodialysis (HD) patients. There have been a few reports on the use of lepirudin, argatroban, or danaparoid in the management of extracorporeal thrombosis (ECT) during dialysis in these patients, because heparin is contraindicated. Here, we report the first long‐term use of bivalirudin to prevent ECT. Our study was conducted at Fahd Bin Jassim Kidney Center in Doha, Qatar. All patients diagnosed with HIT were included. A bivalirudin treatment protocol was developed with the initial dosage and dosage adjustments based on the value of activated partial thromboplastin time (aPTT), the risk of bleeding, and the recurrence of ECT. Eight patients were positive for HIT AB. Among them, three were excluded: two due to the use of warfarin for atrial fibrillation and one due to a negative repeat HIT AB test with no ECT. Five patients who were positive for HIT AB and experienced recurrent ECT events during dialysis were included. These patients were monitored while on bivalirudin protocol for a mean of 4.6 ± 2 months, during which they received a mean number of HD treatments of 66 ± 24. There were no bleeding events or adverse reactions related to bivalirudin during the study. Here, we report the first long‐term successful use of a bivalirudin protocol to prevent ECT in ambulatory HD patients with HIT. This protocol allowed for a simple dosing initiation with easy adjustment based on weight, aPTT, and recurrence of ECT events. The protocol provided excellent safety.